Modelling of Micro Hydropower System for Small Load Application - Azmi, Rasyad; Yazid, Faris; Mahmud, Nizamullah; Hassan, Faradillah; Azhar, Azrini; Salimin, Suriana (Journal of Electronic Voltage and Application, 2022)
The implementation of Movement Control Order (MCO) to curb the spread of covid-19 in Malaysia has resulted in an increased financial burden on the people especially those from the low-income group. Therefore, taking advantage of the promising renewable energy as the free source of electricity could subsequently reduce the financial burden borne by this group. Hence, this paper conducts an analysis using MATLAB/Simulink software, to assess the viability of small-scale hydro turbines in converting potential energy of water heads into electricity for powering small load appliances. The analysis consists of several parts such as the DC generator, converter and charge controller. The data regarding volume of water usage in this study is based on water usage by the author. The result from simulation through the MATLAB software demonstrate a convincing reading in recorded voltage, current and power which indicate this system is feasible for electrification of small load appliances and indicate the potential for future improvement and research.